PENINGKATAN KREATIVITAS MURID PADA PEMBELAJARAN IPAS MENGGUNAKAN PENDEKATAN STEAM TERINTEGRASI SINTAKS PJBL DI KELAS III SDN 07 BELAKANG BALOK KOTA BUKITTINGGI - Putri Ana, Amanda; Engreini, Syofianti; Ulya Akmal, Atika; Wahyuni, Etri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the increase of student creativity through the application of the STEAM approach to social studies learning in grade III of SDN 07 Balik Balok Kota Bukittinggi. This research is a Classroom Action Research (PTK) with a qualitative and quantitative approach involving 25 students. The results of the study showed an increase in each cycle, namely: learning planning in cycle I obtained an average of 90% (SB) and increased in cycle II to 95% (SB); the implementation of teacher aspect learning in the first cycle of 92.25% (SB) increased to 97% (SB) in the second cycle; the pupil aspect in the first cycle of 87.6% (B) increased to 97% (SB) in the second cycle; student creativity in the first cycle of 64.6% (K) increased to 88.6% (SK) in the second cycle; and the results of student knowledge in the first cycle of 89.6% (B) increased to 99.2% (SB) in the second cycle. Thus, the STEAM approach can increase students' creativity in learning science materials on energy sources and changes in the form of energy in grade III of SDN 07 Balik Balok Kota Bukittinggi.